Factors Affecting the Collection of Corporate Income Tax: The Case of Baltic States - Snitkienė, Kamilė; Senkus, Kastytis; Budrionytė, Ramunė (Buhalterinės apskaitos teorija ir praktika, 2018)
[only abstract in English; full article and abstract in Lithuanian] A stable and well-structured tax system is one of the key factors driving economic growth and the attractiveness of the investment environment, ensuring the funds for the fulfillment of state functions. However, tax systems are often criticized and the corporate income tax is one of the most criticized element of the system. The aim of the study is to identify the economic factors affecting the collection of corporate income tax in the Baltic States, the strength and trend of the influence. The changes of corporate income tax rates, the dynamic of collection as well as the dynamic of factors influencing the collection of corporate income tax in the Baltic States were analysed. The impact of GDP, direct foreign investment, export, import, employment on the collection of corporate income tax was analysed as well. The study revealed that corporate income tax collection is strongly or very strongly correlated to GDP. The collection of corporate income tax was strongly correlated with imports in Latvia, while in Estonia a strong correlation with foreign investments was found. The lowest correlation in all countries was observed between corporate income tax collection and employment. Subsequent regression analysis resulted in the creation of one-dimensional regression equations between dependent (corporate income tax collection) and independent (GDP, direct foreign investment, export, import, employment) variables for every Baltic state.